Regression models of dynamic of harmful emissions in the atmosphere og Ukraine - Kovpak, E. O.; Myhailenko, V. G.; Maslennykova /, O. V. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2018)
The paper deals with the analysis of the type and the degree of relationship between the harmful emissions to the atmosphere of Ukraine and indicators of the measurement of gross domestic product: GDP in current prices, GDP in constant prices, "green" GDP.The analysis of the sources structure of harmful emissions has been carried out and it has been shown that economic activity leads to the greatest contamination of the atmosphere. The rating of the industries that cause the greatest environmental damage has been developed on the  basis of the Environmental Account 2015 for the protection of atmospheric air in Ukraine.The methods of correlation analysis are applied. The World Bank and State Statistics Service of Ukraine database is used. The closest correlation dependence  was  found out between the volumes of harmful emissions and GDP of Ukraine in constant prices 2010 in USD.The model of multiple linear regression  for harmful emissions from GDP of Ukraine with the use of dummy-variables has been constructed.Two alternative simple regressions for the volume of harmful emissions have been constructed: with GDP of Ukraine in constant prices or with the "green" GDP of Ukraine. The share of described variation in the model with "green" GDP is higher.